Contesting Almsgiving in Post-New Order Indonesia - Hilman Latief (AJISS, 2014)
This article explores the origin and development of the ideas and practice of zakat (Islamic tax) on salary and identifies how it affects the nature of zakat practice in contemporary Indonesia. The recent trend suggests that Indonesian Muslims are attempting to translate and reinterpret the Islamic concept of social justice by utilizing zakat on salary (zakat profesi) as a discursive center. Despite the fact that this has been the subject of heated debate among Muslim scholars since the 1980s, the Indonesian state has attempted to make its payment mandatory by enacting zakat regulations at both the provincial and district levels. This new phenomenon is stimulating new debates among the countryâ€™s Islamic scholars over the legality, from a jurisprudential aspect, of imposing zakat regulations on civil servants. Some believe that zakat practice has been precisely prescribed in the Qurâ€™an and Sunnah and thus such an â€œinnovationâ€ is not necessary; others consider zakat to belong to that part of the Islamic ethical and economic system that is open to reinterpretation and innovation. Disagreement among Islamic scholars, competition between civil society organizations and state agencies, and tension between the government (political authorities) as a policymaker and people at the grassroots level are indications of how almsgiving is contested in democratic Indonesia.